Current-mediated synchronization of a pair of beating non-identical flagella. (28th March 2019) - Dotsenko, V S; Maciolek, A; Oshanin, G; Vasilyev, O; Dietrich, S
Abstract: The basic phenomenology of experimentally observed synchronization (i.e. a stochastic phase locking) of identical, beating flagella of a biflagellate alga is known to be captured well by a minimal model describing the dynamics of coupled, limit-cycle, noisy oscillators (known as the noisy Kuramoto model). As demonstrated experimentally, the amplitudes of the noise terms therein, which stem from fluctuations of the rotary motors, depend on the flagella length. Here we address the conceptually important question which kind of synchrony occurs if the two flagella have different lengths such that the noises acting on each of them have different amplitudes. On the basis of a minimal model, too, we show that a different kind of synchrony emerges, and here it is mediated by a current carrying, steady-state; it manifests itself via correlated 'drifts' of phases. We quantify such a synchronization mechanism in terms of appropriate order parameters Q and Q  —for an ensemble of trajectories and for a single realization of noises of duration , respectively. Via numerical simulations we show that both approaches become identical for long observation times  . This reveals an ergodic behavior and implies that a single-realization order parameter Q  is suitable for experimental analysis for which ensemble averaging is not always possible.